2021
DOI: 10.3390/ijgi10030112
|View full text |Cite
|
Sign up to set email alerts
|

Saline-Soil Deformation Extraction Based on an Improved Time-Series InSAR Approach

Abstract: Significant seasonal fluctuations could occur in the regional scattering characteristics and surface deformation of saline soil, and cause decorrelation, which limits the application of the conventional time-series InSAR (TS-InSAR). For extending the saline-soil deformation monitoring capability, this paper presents an improved TS-InSAR approach, based on the interferometric coherence statistics and high-coherence interferogram refinement. By constructing a network of the refined interferograms, high-accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…But in the dry season, the high coherences appear again between November and the next April or May. This result proves that the interferometric coherences decrease dramatically due to the increase in precipitation from the dry season to the rainy season (Rui et al, 2021;Xiang et al, 2021;Xiang et al, 2022). However, thousands of average interferometric coherence coefficients are needed for the calculation for further analysis; such a heavy computation requirement is not suitable for long-term monitoring.…”
Section: Interferogram Seasonal Filtering and High-coherence Interfer...mentioning
confidence: 72%
See 4 more Smart Citations
“…But in the dry season, the high coherences appear again between November and the next April or May. This result proves that the interferometric coherences decrease dramatically due to the increase in precipitation from the dry season to the rainy season (Rui et al, 2021;Xiang et al, 2021;Xiang et al, 2022). However, thousands of average interferometric coherence coefficients are needed for the calculation for further analysis; such a heavy computation requirement is not suitable for long-term monitoring.…”
Section: Interferogram Seasonal Filtering and High-coherence Interfer...mentioning
confidence: 72%
“…The previous studies found that the interferometric coherence coefficients in these similar saline mudflat areas have seasonal changes. As shown in Figure 4 (by setting the temporal baseline threshold for 400 days that includes a whole year and the perpendicular spatial baseline threshold for 200 m, a total of 2,921 interferograms are formed with 119 Sentinel-1A images acquired from 2015 to 2020) (Xiang et al, 2021), in the rainy season, the high interferometric coherences of interferograms mainly occur between June and November and disappear dramatically after November. But in the dry season, the high coherences appear again between November and the next April or May.…”
Section: Interferogram Seasonal Filtering and High-coherence Interfer...mentioning
confidence: 99%
See 3 more Smart Citations